Jogo de papéis na pré-escola: uma análise de “Psicologia do Jogo” na perspectiva da aprendizagem dialógica - Oliveira, Jéssica de (Universidade Federal de São Carlos, 2024)
The general objective of this course completion work was to analyze the ‘game’ activity presented by Daniil B. Elkonin, in his book “Psychology of Game”, identifying potential contributions to promote the instrumental dimension of learning with preschool children. It starts from the identification of gaps in the understanding of the way in which young children perceive and interpret the reality around them and problematizes the elements of interactions and play proposed in Brazilian legislation and educational literature that address preschool. Based on the framework of dialogic learning, it considers the relevance of studying classic works of Historical-Cultural Psychology, which support scientific knowledge, in order to support pedagogical actions aimed at expanding the instrumental dimension of learning and promoting cognitive development, children's social and affective aspects in contemporary preschool. The study was bibliographic in nature and used content analysis techniques applied to the selected book. The results were organized into four categories: 1) Conceptualization; (2) Theoretical Discussion; (3) Examples; and (4) Relationship with other concepts. The conclusions indicated the crucial role of social role playing during the preschool period, showing that the child not only engages playfully with this activity, but also appropriates functions and norms of behavior present in interactions, which contributes to the formation of your personality.

El objetivo general de este trabajo de finalización del curso fue analizar la actividad de “juego” presentada por Daniil B. Elkonin, en su libro “Psicología del juego”, identificando posibles contribuciones para promover la dimensión instrumental del aprendizaje con niños en edad preescolar. Parte de la identificación de lagunas en la comprensión de la manera en que los niños pequeños perciben e interpretan la realidad que los rodea y problematiza los elementos de interacción y juego propuestos en la legislación y la literatura educativa brasileñas que abordan la educación preescolar. Partiendo del marco del aprendizaje dialógico, se considera la relevancia de estudiar obras clásicas de la Psicología Histórico-Cultural, que sustentan el conocimiento científico, con el fin de sustentar acciones pedagógicas encaminadas a ampliar la dimensión instrumental del aprendizaje y promover el desarrollo cognitivo, social y afectivo de los niños. Aspectos en el preescolar contemporáneo. El estudio fue de carácter bibliográfico y utilizó técnicas de análisis de contenido aplicadas al libro seleccionado. Los resultados se organizaron en cuatro categorías: 1) Conceptualización; (2) Discusión Teórica; (3) Ejemplos; y (4) Relación con otros conceptos. Las conclusiones señalaron el papel crucial del juego de roles sociales durante el período preescolar, demostrando que el niño no sólo se involucra lúdicamente con esta actividad, sino que también se apropia de funciones y normas de comportamiento presentes en las interacciones, lo que contribuye a la formación de su personalidad.
Role playing in preschool: an analysis of “Psychology of the Game” from the perspective of dialogical learning
Juego de roles en la pre escuela: un análisis de la “Psicología del juego” desde la perspectiva de aprendizaje dialógico
Keywords: Jogo de papeis; Psicologia do Jogo; Elkonin; Pré-escola; Aprendizagem dialógica; Role play; Game Psychology; Pre school; Dialogical learning; Juego de roles; Psicología del juego; Aprendizaje dialógico; Pre escuela; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM